The philosophy of rhetoric - Campbell, George, 1719-1796 (Landmarks in rhetoric and public address., 1988)
Here, after a quarter century of additional study and reflection, Bitzer presents a new critical edition of George Campbell's classic. Bitzer provides a more complete review and assessment of Campbell's work, giving particular emphasis to Campbell's theological views, which he demonstrates played an important part in Campbell's overall view of reasoning, feeling, and moral and religious truth. The Rhetoric is widely regarded as the most important statement of a theory of rhetoric produced in the 18th century. Its importance lies, in part, in the fact that the the.